2009
DOI: 10.1002/art.24431
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydiae as etiologic agents in chronic undifferentiated spondylarthritis

Abstract: Objective. The majority of patients with Chlamydia-induced reactive arthritis do not present with the classic triad of arthritis, conjunctivitis/iritis, and urethritis. Moreover, acute chlamydial infections are often asymptomatic. The aim of the present study was to assess the prevalence of synovial Chlamydia trachomatis and Chlamydia pneumoniae infections in patients with chronic undifferentiated spondylarthritis (uSpA).Methods. Study patients met the European Spondylarthropathy Study Group criteria for SpA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 29 publications
5
56
0
3
Order By: Relevance
“…These DAMPs could activate TLRs to elicit the inflammatory reaction and ectopic enchondral bone formation in AS spine [32]. Although bacterial infection such as Chlamydia could cause chronic arthritis [40], it is still premature to conclude that bacterial infection can cause AS [41]. Conversely, evidence suggests that AS disease activity became worse, following the different bacterial infections such as Salmonella, Yersinia, Campylobacter and Chlamydia [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…These DAMPs could activate TLRs to elicit the inflammatory reaction and ectopic enchondral bone formation in AS spine [32]. Although bacterial infection such as Chlamydia could cause chronic arthritis [40], it is still premature to conclude that bacterial infection can cause AS [41]. Conversely, evidence suggests that AS disease activity became worse, following the different bacterial infections such as Salmonella, Yersinia, Campylobacter and Chlamydia [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicate that approximately 5% of those with a genital chlamydial infection will develop acute ReA, and about half of these will proceed to chronicity [30]. Further, published data indicate that 20%-40% of individuals with inflammatory arthritis but no documented prior genital infection with C. trachomatis who are given a diagnosis of uSpA, oligoor mono-arthritis are PCR positive in synovial tissue and/or fluid for C. trachomatis DNA [31,32]. A study published in 2009 reported that C. trachomatis DNA in ReA and uSpA patients is rather high (100% and 64%, respectively) [13], while other studies reported relatively low frequencies (25%) [11].…”
Section: Discussionmentioning
confidence: 99%
“…It should be suspected when there is a recent history of diarrhea, cystitis, conjunctivitis, unexplained genitourinary symptoms, prostatitis or chlamydial infection (17). Some studies have raised the possibility that C. pneumoniae, like C. trachomatis, may be a causative agent in ReA (18)(19)(20) and as both are often asymptomatic (21,22), the causative trigger is less clinically apparent in many cases (23). Genetic factors and infections have a very strong correlation with the development of ReA (24).…”
Section: Discussionmentioning
confidence: 99%